Studi Literature: Good Governance dan Ketahanan Keuangan pada Organisasi Nirlaba - Wahyu Setiyarso, Reinka Sekar; Yuhertiana, Indrawati (SUSTAINABLE, 2025)
Non-profit organizations must apply good governance principles. This is because the organization must become a professional organization by applying these principles. The implementation of good governance will improve financial control in the organization's operations. The purpose of this study is to determine the extent of the development of research on good governance in non-profit organizations in order to maintain the financial stability of the organization. This research is a literature review research that uses bibliometric methods to map previous research with a time span of 2020 to 2024. After the selection process using Microsoft Excel, a total of 43 articles were obtained, then the data will be analyzed through the VOSviewer ver.1.6.20 application. The results of the keyword restriction process are then grouped into 3 clusters, such as organization, transparency, good corporate governance. The results of the mapping carried out also show that good governance in non-profit organizations is still rarely researched so that the author hopes that this mapping can become and add information for future researchers on the topic of good governance in non-profit organizations. Researchers can analyze the implementation of good governance and what obstacles or obstacles the organization faces in its implementation.